The Outcomes of the Community Cooking Workshops for International Students at Simon Fraser University - Luongo, Gabriella; Tucker, Rochelle; Hutchinson, Crystal; Dhaliwal, Rosie (Journal of International Students, 2018)
The Community Cooking Workshops (CCWs) are free, bi-weekly, hands-on, cooking and nutrition education workshops for international students facilitated by the Simon Fraser University (SFU) Peer Health Educators (PHEs). The impacts of the CCWs on international student nutrition knowledge, behavior change, and social outcomes were examined. Data was collected and coded from five Spring 2016 CCWs through workshop evaluation forms (n=87, 93% response rate) and nine semi-structured interviews with international student participants. Participants reported changes in eating behavior and knowledge (all food should be consumed in moderation, with variety) and improved sense of community. Future research should assess the long-term impacts of cooking workshops in postsecondary institutions on diet quality, cooking skills, social connectedness, and international student wellbeing